Small scale abundance and movement of Atka mackerel and other Steller sea lion groundfish prey in the Western Aleutian Islands - Susanne McDermott (Research Workspace, 2014)
The dataset was collected in the central and western Aleutian Islands, Alaska during 2014 and 2015 as part of a large-scale tagging effort to estimate Atka mackerel abundance and movement at several locales. The dataset describes locations and lengths of tagged fish as well as conductivity, salinity, and temperature data. The dataset consists of 9 files: 1305_TagsRecovered.csv 1305_TagsReleased.csv 1305_Specimen.csv 1305_SeededTags.csv 1305_Mortality.csv 1305_MasterHaul.csv 1305_Lengths.csv 1305_CTD.csv 1305_Catch.csv